Bone mineral density and content of collegiate throwers: Influence of maximum strength - Whittington, J.; Schoen, E.; Labounty, L. L.; Hamdy, R.; Ramsey, M. W.; Stone, M. E.; Sands, W. A.; Haff, G. G.; Stone, M. H. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: Bone changes in size and density in response to different levels of stress. Alterations to bone mineral density (BMD) appear to occur in a site specific manner. Even though BMD has been examined in many populations there is a paucity of data looking at strength-power athletes, such as throwers. Therefore, the purpose of this study was to examine the BMD of a group of USA Division I collegiate throwers (e.g. shot put, discus, etc.). METHODS: Seven throwers (4 males; 3 females) who were 19.0 ± 0.9 years had their BMD compared to an age matched control group (n=14; 8 women and 6 men) and normative data. BMD was measured with dual X-ray absorptometry. Potential right/left side and sex difference in BMD were also examined. Maximal isometric strength was assessed using a mid-thigh pull while standing on a forceplate which generated force-time curves. Peak force (PF) and normalized peak force (PFa) were then correlated with BMDs. RESULTS: Generally, throwers had denser bones with male throwers tending to have a greater total BMD (P=0.05). The dominant arm BMD was slightly greater when compared to non-dominant arm (P=0.05). Furthermore, total body BMD was related to PF (r=0.68, r2 =0.46) and PFa (r=0.56, r2=0.31). CONCLUSIONS: Throwers have greater BMDs than non-athletes and most other athletes. However, throwers only showed a small indication of sidedness. It is likely that the BMDs observed in this study stem from the training intervention (e.g. whole body heavy lifting) undertaken by this population.